Antibacterial Activity against Enterococcus faecium, Enterococcus faecalis and Inhibitory Activity of Monoamine Oxidase A & B by Persea americana “Avocado” Seed Extracts - Nogbou, N-D.; Mkhombo, Z.T.; Olivier, M.T.; Ogunrombi, M.O.; Maseko, R.B.; Musyoki, A.M. (Asian Journal of Chemistry, 2021)
This study reported various Persia americana seed extracts for the presence and total content of phytochemicals, antibacterial activity and inhibitory activity against monoamine oxidase (MAO) A & B enzymes. Phytochemical studies showed that phenols, flavonoids and tannins were found in all the polar solvents. The highest antibacterial activity was exhibited against Gram-positive bacteria by acetone extract on Enterococcus faecium and methanol extract on Enterococcus faecalis. From the monoamine inhibition experiments, a significant inhibitory activity was observed from ethanolic extracts against MAO-A and from n-hexane extracts against MAO-B. This study demonstrates the antimicrobial activity of P. americana seed extracts against enterococci bacteria, E. faecium and E. faecalis. This finding offers hope of a potential new antibacterial compound in the treatment of these multidrug resistant bacteria.